The ways to increase of staff labor productivity in agriculture - Koitanova, A.G.; Zholmukhanova, A.Zh.; Alpeissova, S.E. (BUKETOV BUSINESS REVIEW, 2017)
The article presents the process of human resources strategic management in agriculture, its clear strategy, the relationship between policy and strategy formed by management system. Stages of implementation of the human resources strategic management in agriculture are also shown. Marketing strategy classification was reviewed in given article, which are focused on reducing of production costs i.e. strategy oriented on reducing production costs; strategy on improving of the quality of services and goods; innovational strategy, strategy of deep penetration into the market, etc. Measures on skills improvement are considered and presented: systematic training of agricultural workers; continuous exchange of experience and knowledge; ability to obtain additional education in higher and secondary educational institutions; dual education; site training at production sites. The ways of qualification improvement of human resources were proposed in JSC «Aktyk» in order to improve the process of human resources strategic management. Also the influences of highly-qualified staff on production volumes are shown based on data of JSC «Aktyk», «Rodina» LLP, «Novokubanskoe» LLP. A linear pair regression equation, the pair correlation coefficient, net regression coefficient is calculated. According to the results of the analysis and the study of the human resources strategic management problems have been identified such as the absence of a single clear staff selection and recruitment systems; ineffective setting of clear organizational goals.